2017
DOI: 10.4103/ccd.ccd_886_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of caries status in primary and permanent molars in 7–8-year-old schoolchildren of shimla using caries assessment spectrum and treatment index

Abstract: Background:A new epidemiological index is introduced for full assessment of dental caries which is known as caries assessment spectrum and treatment (CAST). “Spectrum” is considered backbone of this index as it covers from no lesion to advanced stage progression of caries. We aimed to evaluate and compare the status of caries in primary and permanent molars of 7–8-year-old schoolchildren of Shimla using CAST index and to find if any correlation exists between the status of caries in evaluated teeth.Methods:Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
(36 reference statements)
6
9
3
Order By: Relevance
“…The prevalence of subjects with caries-free permanent molar teeth was high, which is in line with the results of a study by Dorenia et al, in Shimla. [23] but is in contrast to the findings of a study by Shyam et al, in 2017 [24] reporting a lower level of caries-free in the first permanent molars in India. Considering a recent guideline on fissure sealant, it is strongly recommended that the use of sealants should be considered in permanent molars with both sound occlusal surfaces and non-cavitated occlusal carious lesions in children and adolescents [25].…”
Section: Discussioncontrasting
confidence: 65%
“…The prevalence of subjects with caries-free permanent molar teeth was high, which is in line with the results of a study by Dorenia et al, in Shimla. [23] but is in contrast to the findings of a study by Shyam et al, in 2017 [24] reporting a lower level of caries-free in the first permanent molars in India. Considering a recent guideline on fissure sealant, it is strongly recommended that the use of sealants should be considered in permanent molars with both sound occlusal surfaces and non-cavitated occlusal carious lesions in children and adolescents [25].…”
Section: Discussioncontrasting
confidence: 65%
“…In line with our findings, Doneria et al observed that 14.28% of primary molars were with CAST code 6, while only 0.6% of permanent molars suffered such morbidity [32]. Moreover, in a cross-sectional study of 4642 patients from the institute of antral Gujarat, it was found that the prevalence of dental caries was the highest (44.3%) in the age group 21-40, while the lowest prevalence was found in the geriatric population above the age of 80 [33].…”
Section: Associations Of Age and Sex With Sos Teethsupporting
confidence: 93%
“…In our study, the correlation between the caries status of the upper and lower FPMs was emphasized at the age of 7-8 years, because the anterior teeth are in the state of exchange. Hence, the exclusion of incisors and canines in this study provided a homogeneous sample of the population [13,16,23]. It was also observed that the Spearman rank correlation coefficient was statistically significant on all quadrants but showed the strongest correlation between the contralateral FPM teeth of the upper and lower arch.…”
Section: Discussionmentioning
confidence: 69%
“…The prevalence of sound FPMs was reported that 33% among 9-year-old Saudi school children [15]. Whereas it has been reported that 89.7% of Indian school children had caries-free FPM teeth among 7-8 years old [16]. The prevalence of FPM caries (diagnosed according to the WHO criteria) among 9-year-old Saudi schoolchildren has been reported as 67% [15,17].…”
Section: Discussionmentioning
confidence: 99%